2022
DOI: 10.1515/tjb-2022-0123
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between serum vitamin D and antibody response following two doses of inactivated COVID-19 vaccine

Abstract: Objectives Low vitamin D levels are associated with the severity and mortality of COVID-19 infection. Nevertheless, the relationship between the 25-hydroxyvitamin D [25(OH)D] levels and the antibody response following COVID-19 vaccination is not fully elucidated. Herein, we explored the relationship between SARS-CoV-2 IgG (sCOVG) and 25(OH)D. Methods In this prospective observational case-control study, we used an automated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…In this case, we obtained statistically significant data. Incidentally, higher antibody titers were detected in patients with low vitamin D levels after vaccination against Human Papillomavirus [59]. Moreover, we determined that vitamin D levels three to four weeks after vaccination had a negative correlation with a decline in anti-SARS-CoV-2 IgG antibodies titer during six months after vaccination, and this finding was confirmed by multivariate binary logistic regression analysis.…”
Section: Discussionsupporting
confidence: 52%
“…In this case, we obtained statistically significant data. Incidentally, higher antibody titers were detected in patients with low vitamin D levels after vaccination against Human Papillomavirus [59]. Moreover, we determined that vitamin D levels three to four weeks after vaccination had a negative correlation with a decline in anti-SARS-CoV-2 IgG antibodies titer during six months after vaccination, and this finding was confirmed by multivariate binary logistic regression analysis.…”
Section: Discussionsupporting
confidence: 52%
“…Our results are in line with what most other report concerning the association between vitamin D status, deficiency and/or supplementation and SARS-CoV-2 immune responses following vaccination in healthy adults. The majority of previous studies have similarly found no association between vitamin D and different immune endpoints following COVID-19 vaccination, such as binding antibodies, neutralizing antibodies, antibody decline and cellular responses [ 24 , 25 , 26 , 27 ]. Yet, a limited pair of studies report conflicting findings.…”
Section: Discussionmentioning
confidence: 99%
“…Here, contrasting findings exist. Most studies report that vitamin D levels and/or supplementation are not associated with COVID-19 vaccine immunogenicity [ 24 , 25 , 26 , 27 ]. However, some report a positive association between vitamin D levels/supplementation and COVID-19 vaccine antibody responses [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%